2021
DOI: 10.1101/2021.02.03.429507
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diffusion of the disordered E-cadherin tail on β-catenin

Abstract: Specific protein interactions typically require well-shaped binding interfaces. Here, we report a cunning exception. The disordered tail of the cell-adhesion protein E-cadherin dynamically samples a large surface area of the proto-oncogene β-catenin. Single-molecule experiments and molecular simulations resolve these motions with high resolution in space and time. Contacts break and form within hundreds of microseconds without dissociation of the complex. A few persistent interactions provide specificity where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 94 publications
(116 reference statements)
3
20
1
Order By: Relevance
“…This effect increases in magnitude with increasing ionic strength and is ablated when the five charged residues are mutated to alanine in the 5X construct. Intriguingly the results of the recent single-molecule study of the E-cadherin-βcatenin interaction led to a similar suggestion, whereby there is the continuous detachment and reattachment of local E-cadherin segments [57]. We share the authors' conclusion of a Velcro-like design of many weak contacts on top of a few persistent interactions.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…This effect increases in magnitude with increasing ionic strength and is ablated when the five charged residues are mutated to alanine in the 5X construct. Intriguingly the results of the recent single-molecule study of the E-cadherin-βcatenin interaction led to a similar suggestion, whereby there is the continuous detachment and reattachment of local E-cadherin segments [57]. We share the authors' conclusion of a Velcro-like design of many weak contacts on top of a few persistent interactions.…”
Section: Discussionsupporting
confidence: 78%
“…Similar behaviour has been observed in the crystal structures of other β-catenin complexes, providing tantalising hints to the underlying mechanisms of recognition [10,21,23,[26][27][28]56]. Most recently, a single-molecule study by Hofmann and co-workers on the interaction between β-catenin and E-cadherin revealed a rugged energy landscape of E-cadherin with many shallow minima, a fuzzy complex, and a mechanism of intrachain diffusion of E-cadherin on β-catenin [57]. Here, we used site-directed mutagenesis and kinetic analysis to explore the significance of this plasticity in the β-catenin-TCF7L2 complex and to define the mechanism of association between the two proteins.…”
Section: Figuresupporting
confidence: 64%
See 2 more Smart Citations
“…[62] identified a fuzzy complex, where segments of E-cadherin (E-cad) diffuse dynamically royalsocietypublishing.org/journal/rsob Open Biol. 11: 210222 with high affinity over a large surface area of β-cat, in a manner distinct to the interactions observed between β-cat and Tcf4 [42][43][44]62]. β-cat is a cytoplasmic multifunctional repeat protein consisting of three domains: a central region domain, consisting of 12 imperfect armadillo domains which serve as the major interaction domain; a disordered N-terminal domain and a disordered CTD [62][63][64][65].…”
Section: Highly Dynamic E-cadherin Tail and β-Cat Interactionmentioning
confidence: 99%